2010
DOI: 10.3802/jgo.2010.21.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total plasma lysophosphatidic acid and serum CA-125 as a tumor marker in the diagnosis and follow-up of patients with epithelial ovarian cancer

Abstract: Objective:To evaluate the role of lysophosphatidic acid (LPA) as a tumor marker in diagnosis and follow-up of patients with epithelial ovarian cancer. Methods: Eighty-seven epithelial ovarian cancer patients, 74 benign ovarian tumor patients, and 50 healthy women were enrolled in the study. Twenty-nine of 87 epithelial ovarian cancer patients were followed up for 6 cycles of paclitaxel-carboplatin chemotherapy. CA-125 and total plasma LPA levels were measured preoperatively and before each chemotherapy cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…LPA was first implicated in human oncogenesis, as this biolipid is present at high levels in the ascitic fluid of ovarian cancer patients (Mills et al, 1990;Xu et al, 1995). Consistently, higher plasma LPA level was reported in ovarian cancer patients compared with patients with benign ovarian masses and healthy subjects (Xu et al, 1998;Bese et al, 2010;Sedlakova et al, 2011). Further, ovarian cancer cells have been known to secrete LPA to make enriched environment (Fang et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…LPA was first implicated in human oncogenesis, as this biolipid is present at high levels in the ascitic fluid of ovarian cancer patients (Mills et al, 1990;Xu et al, 1995). Consistently, higher plasma LPA level was reported in ovarian cancer patients compared with patients with benign ovarian masses and healthy subjects (Xu et al, 1998;Bese et al, 2010;Sedlakova et al, 2011). Further, ovarian cancer cells have been known to secrete LPA to make enriched environment (Fang et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies have shown that LPA levels are elevated in the ascites of ovarian cancer patients, most probably due to increased LPA production by cancer cells and the surrounding mesothelium (36,37,(41)(42)(43). The potential contribution of GPAM to this process is not known, thus justifying further investigation into its role in this disease.…”
Section: Discussionmentioning
confidence: 97%
“…LPA is present in multiple body fluids, such as blood [16, 17], saliva [18] and urine [19]. Serum concentrations of LPA are higher than in plasma, which is probably caused by secretion of LPA by activated platelets [20].…”
Section: Introductionmentioning
confidence: 99%